Edge Effects on Vegetation Structure and Resource Use Pattern at Two Community Forests of Surkhet, Nepal - Shahi, Durga; Sharma, Krishna Prasad; Shah, Saroj; Chettri, Mukesh Kumar (Amrit Research Journal, 2022)
This study assessed the forest structure and regeneration at the edge and core parts of two community forests, Ram Janaki and Furkesalli of Surkhet district, Western Nepal, and the forest resources use pattern. Different blocks designated by community forest user groups were considered to designate edge and core strata for stratified random sampling. For vegetation analysis and regeneration of tree 15 circular plots (n = 60) of 10m radii; for shrubs 5m radius subplot and for herbs three 1 m radii subplots within the 10 m radii circular plots were considered. Semi-structured questionnaire approach was employed for the collection of ethnobotanical data. Based on importance value index dominant herbs were Ageratum haustoniaum in edge and Heteropogon contortus core part; dominant shrub were Phoenix acaulis in both community forests (RCF and FCF); and Shorea robusta was dominant tree at edge forest of both RCF and FCF whereas Lagerstroemia parviflora was dominant at FCF coreforest. The species diversity was recorded higher in core parts in both forests. The forests are rich in the diversity of medicinal plants with 26 species under 25 genera and 23 families of which root parts were mostly used as ethnomedicine and mostly for gastrointestinal disorder. Besides medicines, firewood, fodder, fruits, vegetable, timber and bedding material were the other uses of forest resources.